2018
DOI: 10.4467/16890027ap.18.015.10091
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Studies on a Model Tintinnid - Schmidingerella meunieri (Kofoid and Campbell, 1929) Agatha and Strüder-Kypke, 2012 (Ciliophora). I. Somatic Kinetids with Unique Ultrastructure

Abstract: Molecular phylogenies of Oligotrichea currently do not contain all genera and families and display topologies which are often incongruent with morphological findings. In ciliates, the somatic kinetids are rather conserved, i.e., their ultrastructures, particularly the fibrillar associates, often characterise the main groups, except for the choreotrichids. Four different kinetid types are found in protargol-stained choreotrichids and used for reconstructing the taxon’s evolution (the “Kinetid Transformation Hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…In L. viride (this study), Strombidiidae (Agatha and Riedel-Lorjé 1997, Agatha 2004b), and the aloricate choreotrichid Strombidinopsis minima (Agatha 2003b), the dikinetids are anticlockwise inclined to the kinety axis (surface view), while clockwise inclined in euplotids (Ruffolo 1976, Wicklow 1983, Morelli et al 1996) and hypotrichs (Grimes and Adler 1976, Wirnsberger-Aescht et al 1989). The dikinetidal basal bodies extend parallel to each other in euplotids (Ruffolo 1976, Wicklow 1983, Lenzi and Rosati 1993) and hypotrichs (Grimes and Adler 1976), while the posterior ventral and left girdle basal bodies of oligotrichid dikinetids are obliquely orientated (this study, Fauré-Fremiet and Ganier 1970, Modeo et al 2003); data for choreotrichids are not available, but will soon be published for a tintinnid (Gruber et al 2018).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In L. viride (this study), Strombidiidae (Agatha and Riedel-Lorjé 1997, Agatha 2004b), and the aloricate choreotrichid Strombidinopsis minima (Agatha 2003b), the dikinetids are anticlockwise inclined to the kinety axis (surface view), while clockwise inclined in euplotids (Ruffolo 1976, Wicklow 1983, Morelli et al 1996) and hypotrichs (Grimes and Adler 1976, Wirnsberger-Aescht et al 1989). The dikinetidal basal bodies extend parallel to each other in euplotids (Ruffolo 1976, Wicklow 1983, Lenzi and Rosati 1993) and hypotrichs (Grimes and Adler 1976), while the posterior ventral and left girdle basal bodies of oligotrichid dikinetids are obliquely orientated (this study, Fauré-Fremiet and Ganier 1970, Modeo et al 2003); data for choreotrichids are not available, but will soon be published for a tintinnid (Gruber et al 2018).…”
Section: Discussionmentioning
confidence: 95%
“…In tintinnids, the somatic ciliature consists of some dikinetids and many monokinetids, but merely the ultrastructure of monokinetids had been described as yet (Hedin 1976, Laval-Peuto and Brownlee 1986, Laval-Peuto 1994); a detailed investigation on Schmidingerella meunieri will soon be published (Gruber et al 2018). Interestingly, the postciliary ribbons extend parallel to the kinety axis and terminate posteriorly to the second following kinetid, overlapping the postciliary microtubules of the next kinetid; such a pattern is not found in L. viride .…”
Section: Discussionmentioning
confidence: 99%
“…2019 ). Although tintinnids have a long history of taxonomic study ( Müller 1779 ; Haeckel 1866 ), there exists no published data on their MIC or genomic architecture, and only limited transcriptome data exist for Schmidingerella ( Keeling et al. 2014 ), the only tintinnid genus with transcriptome data.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ultrastructure and cyst morphology should also be considered (Gruber et al, 2019). However, our study showed that the molecular data could play an important part in the resolution of the cryptic species, as suggested by Santoferrara and McManus (2017).…”
Section: Establishment Of Cryptic Speciesmentioning
confidence: 78%
“…To resolve this issue, previous studies suggested that the subtle morphological or ecological differences among the species are required, so we can understand their biogeography and ecological niche differentiation ( McManus et al, 2010 ). Moreover, the ultrastructure and cyst morphology should also be considered ( Gruber et al, 2019 ). However, our study showed that the molecular data could play an important part in the resolution of the cryptic species, as suggested by Santoferrara and McManus (2017) .…”
Section: Discussionmentioning
confidence: 99%